Exploring Cognitive and Affective Dimensions of Written Corrective Feedback in Indonesian EFL Writing - Inayah Taqwa, Nurul; Nasmilah, Nasmilah; Rodiana Jubhari, Ria (International Journal of Social Sciences and Humanities, 2025)
This study aims to explore the perceptions of sixth-semester students in the English Language Education Program at UIN Palopo regarding direct and indirect written corrective feedback (WCF), as well as its relation to their motivation in developing English writing skills. The research employed a qualitative approach with a phenomenological design. Data were collected using an online questionnaire via Google Forms, consisting of both multiple-choice and open-ended questions. Thematic analysis was applied to identify key patterns in the students’ responses. The findings reveal that students generally prefer a combination of direct and indirect feedback. Direct feedback was perceived as helpful in clarifying grammatical errors, while indirect feedback encouraged critical thinking and independent revision. WCF was reported to support grammatical accuracy, enhance revision practices, and foster an understanding of writing as a recursive process. Furthermore, the emotional tone of feedback significantly influenced students' motivation. Constructive and empathetic feedback boosted confidence and engagement, whereas overly critical or vague feedback contributed to confusion and decreased motivation. These results highlight the importance of feedback strategies that are not only pedagogically appropriate but also emotionally responsive, to support students’ writing development and sustain motivation in the context of foreign language learning.